High-power versus low-power laser settings during endoscopic stone disease management: a systematic review from the EAU endourology section : review - Spinos, Theodoros; Somani, Bhaskar K.; Tatanis, Vasileios; Skolarikos, Andreas; Tokas, Theodoros; Knoll, Thomas; Peteinaris, Angelis; Vagionis, Athanasios; Liatsikos, Evangelos; Kallidonis, Panagiotis (World journal of urology, 2025)
Optimal laser settings during endoscopic stone disease management still represents a debatable issue. The aim of this systematic review is to summarize all existing evidence regarding the comparison of high-power (HP) versus low-power (LP) laser settings during different endoscopic lithotripsy procedures.
Online veröffentlicht: 16. December 2024
Gesehen am 22.04.2025